A remarkable new species of Callulina (Amphibia: Anura: Brevicipitidae) with massive, boldly coloured limb glands - Menegon, Michele; Gower, David J.; Loader, Simon P. (Zootaxa, 2011)
A large new species of Callulina is described from a series of 22 specimens from the montane and upper montane forest of the Nguru Mountains, Tanzania. The most striking features of Callulina meteora sp. nov. are the massive and boldly coloured glands on the arms and legs and a metallic sheen to the skin. The new species is distinguished further on the basis of acoustic and molecular data. The position, size and conspicuousness of the enlarged glands in the new species are strikingly similar to those of Nectophrynoides viviparus, a toad found also in the Eastern Arc Mountains of Tanzania. The new species is known from a single forest reserve and is of high conservation concern.